2017
DOI: 10.1088/1361-6595/aa9304
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond surface dielectric barrier discharge in atmospheric pressure air: I. measurements and 2D modeling of morphology, propagation and hydrodynamic perturbations

Abstract: A parallel 2D code for modeling nanosecond surface dielectric barrier discharge (nSDBD), combining a discharge description, detailed kinetics and hydrodynamics, is developed and validated. A series of experiments and numerical modeling for a single pulse nSDBD in atmospheric pressure air at a voltage amplitude of 24 kV have been performed. The measured and calculated velocity of the discharge front, electrical current, 2D map of N 2) emission and hydrodynamic perturbations caused by the discharge on the time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 54 publications
9
121
0
Order By: Relevance
“…Here, j ey , j py are the wall-normal (y) component of current density of electrons and positive ions respectively, and γ is the secondary electron emission coefficient, which is set to γ = 0.05 in the present study. Note that we have also carried out numerical tests using two other boundary conditions: 1) the boundary condition described in Zhu et al, 20 i.e., a combination of zero gradient of flux for flow towards boundary and zero flux for flow away from boundary; 2) zero-diffusion flux for both flows towards and away from boundary. In both cases, secondary electron emission is added as described above.…”
Section: B Computational Domain and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, j ey , j py are the wall-normal (y) component of current density of electrons and positive ions respectively, and γ is the secondary electron emission coefficient, which is set to γ = 0.05 in the present study. Note that we have also carried out numerical tests using two other boundary conditions: 1) the boundary condition described in Zhu et al, 20 i.e., a combination of zero gradient of flux for flow towards boundary and zero flux for flow away from boundary; 2) zero-diffusion flux for both flows towards and away from boundary. In both cases, secondary electron emission is added as described above.…”
Section: B Computational Domain and Boundary Conditionsmentioning
confidence: 99%
“…In order to understand the discharge process and obtain the spatial and temporal distribution of generated body force and heat, experimental and numerical studies on SDBD plasma actuators have extensively been conducted. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Experimental results show that the dielectric barrier discharge consists of numerous micro-discharges with a short duration of some 10 ns. The discharge patterns on the dielectric surface depend on the polarity of the applied voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronous start, within 0.2 ns, of the streamers from the edge of the high-voltage electrode and propagation along the dielectric provide a synchronous energy relaxation with generation of weak shock waves near the surface of the dielectric. Numerical modeling of the nSDBDs developed during last 10 years, provides a deep insight into physics of the nanosecond surface discharges [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The main properties of dielectric materials are dielectric constant, thermal conductivity, electric volume resistivity, and specific heat. In the present work, the effects of dielectric materials are studied by changing the dielectric constant, as in the previous studies [11,14]. As a result, the effects of the dielectric constant (ε) and dielectric barrier thickness (td) are investigated in the following.…”
Section: Effects Of Dielectric Barriermentioning
confidence: 98%
“…There are few investigations on the effects of dielectric barrier. The dielectric constant and the dielectric barrier thickness are the two dominant parameters that affect the discharge characteristics; they have been studied in [11,12,13,14] and [11,13,15,16], respectively. It was found that the current and the surface charge density on the dielectric barrier surface increase with the dielectric constant.…”
Section: Introductionmentioning
confidence: 99%